Film, television and the psychology of the social dream - Rieber, Robert W. (Springer New York, 2014)
From the flickering images of the earliest silent films to today's billion-dollar blockbusters, films have captivated the public's eyes, hearts, and psyches. Reflecting - and often creating - the tenor of their times, they combine layers of symbolic and metaphorical images to make a stronger internal impact on their viewers than the still image or the printed word. The compelling pages of Film, Television and the Psychology of the Social Dream illuminate the profound emotional processes involved as films inform and transform our unconscious and conscious minds. Drawing on original and classic scholarship in its field, this provocative volume analyzes these interactions through a wide array of influential films, including pioneering German expressionist works, the Star Trek cycle, and The Godfather. Movies' transformative role in molding philosophies and ethics is shown as the larger meanings of public heroes, stars, fears, and desires evolve, and as salient genres embody more than simply a good story. But despite this century of evolution, the authors assert, one thing remains constant: the critical place of film in communicating individual dreams as well as the shared dreams of a society. Among the featured topics:  The cult of celebrity: how Hollywood created reality. Mental illness and "the shrink" in film. Science fiction: aliens out there, aliens in us. Organized crime and the mass media. Bourne, Bond, and beyond: the significance of the spy. Archetypes: inventors, detectives, warriors. Film, Television and the Psychology of the Social Dream will interest social and clinical psychologists as a noteworthy testament to the human imagination in transmitting and processing culture.